Cervical Spine Injury and Subsequent Cerebellar Ischemia in a Post-Trauma Patient - Md Imdadul Hoque Chowdhury; Saifulla Al Kafi; AKM Ferdous Rahman; Mohammad Salim (Bangladesh Critical Care Journal, 2025)
Cerebellar infarction is a rare but significant complication following cervical spine trauma, particularly in cases involving vertebral artery injury. We report a case of a 45-year-old male who developed acute cerebellar infarction after a road traffic accident resulting in cervical spine injury. MRI confirmed the infarction and MR angiography was advised to diagnose underlying vertebral artery dissection. Prompt diagnosis with either CT angiography or MR angiography and multidisciplinary management, including antithrombotic therapy and cervical spine stabilization, lead to significant neurological recovery. Bangladesh Crit Care J March 2025; 13 (1): 60-61